2022
DOI: 10.3389/fsurg.2022.917776
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of TIMELESS Predicts Poor Prognosis: A Potential Therapeutic Target for Skin Cutaneous Melanoma

Abstract: BackgroundSkin cutaneous melanoma (SKCM) is the most lethal skin cancer with an increasing incidence worldwide. The poor prognosis of SKCM urgently requires us to discover prognostic biomarkers for accurate therapy. As a regulator of DNA replication, TIMELESS (TIM) has been found to be highly expressed in various malignancies but rarely reported in SKCM. The objective of this study was to evaluate the relationship between TIM and SKCM tumorigenesis and prognosis.MethodsWe obtained RNA sequencing data from TCGA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…TIMELESS is a member of the replication fork complex that promotes fork stabilization and prevents the collapse of the stalled replication fork 35,36 . TIMELESS is frequently overexpressed in multiple cancers 37‐39 . Recent research has shown that TIMELESS is overexpressed in CC and regulates cell proliferation and cisplatin sensitivity, suggesting that TIMELESS is an attractive target for cisplatin sensitizers in CC, 40 and the upregulation of TIMELESS is correlated with poor overall survival and disease‐free survival 41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TIMELESS is a member of the replication fork complex that promotes fork stabilization and prevents the collapse of the stalled replication fork 35,36 . TIMELESS is frequently overexpressed in multiple cancers 37‐39 . Recent research has shown that TIMELESS is overexpressed in CC and regulates cell proliferation and cisplatin sensitivity, suggesting that TIMELESS is an attractive target for cisplatin sensitizers in CC, 40 and the upregulation of TIMELESS is correlated with poor overall survival and disease‐free survival 41 .…”
Section: Discussionmentioning
confidence: 99%
“…35,36 TIMELESS is frequently overexpressed in multiple cancers. [37][38][39] Recent research has shown that TIMELESS is overexpressed in CC and regulates cell proliferation and cisplatin sensitivity, suggesting that TIMELESS is an attractive target for cisplatin sensitizers in CC, 40 and the upregulation of TIMELESS is correlated with poor overall survival and disease-free survival. 41 Our study is the first to reveal that PAX1 negatively regulates TIMELESS and suppresses the WNT signaling pathway via the TIMELESS/TCF/ β-catenin axis, which confirmed the role of a tumor suppressor gene for PAX1.…”
Section: Discussionmentioning
confidence: 99%